2007
DOI: 10.1677/joe-07-0058
|View full text |Cite
|
Sign up to set email alerts
|

Antibody-induced modulation of TSH receptor post-translational processing

Abstract: The post-translational processing of the TSH receptor (TSHR) includes intra-molecular cleavage with the loss of a 50 amino acid ectodomain region and the formation of two subunits (a and b), followed by likely a subunit shedding. TSHR antibodies (TSHR-Abs), which are directed at the ectodomain, may influence thyroid function by stimulating or inhibiting TSHR signaling or may bind without any such influence (the neutral group of antibodies). When we examined the characteristics of a series of monoclonal TSHR-Ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 34 publications
0
15
0
Order By: Relevance
“…After many years of studying serum IgG from patients with GD, the most precise delineation of the characteristics of TSHR-Abs has resulted from the analysis of monoclonal antibodies to the TSHR derived from patients with GD or from rodents immunized with the TSHR [2931]. Three varieties of TSHR-Ab are present in most patients with GD; stimulating, blocking and neutral antibodies (Fig.…”
Section: Tsh Receptor Antibodiesmentioning
confidence: 99%
“…After many years of studying serum IgG from patients with GD, the most precise delineation of the characteristics of TSHR-Abs has resulted from the analysis of monoclonal antibodies to the TSHR derived from patients with GD or from rodents immunized with the TSHR [2931]. Three varieties of TSHR-Ab are present in most patients with GD; stimulating, blocking and neutral antibodies (Fig.…”
Section: Tsh Receptor Antibodiesmentioning
confidence: 99%
“…As mentioned above (Section VIII.C.4), neutral hamster mAbs were observed to inhibit TSHR cleavage into subunits, as detected by the flow cytometric, dual mAb approach (80). Remarkably, rather than being neutral, these TSHR mAbs were reported to possess unusual and unexpected functions, namely the ability to signal via multiple pathways not utilized by TSH and not involving Gs␣ (33).…”
Section: "Neutral" Antibodies and Tshr Intramolecular Cleavage Intmentioning
confidence: 78%
“…Some monoclonal TSHR antibodies derived from hamsters vaccinated with adenovirus expressing the human TSH holoreceptor neither activate the receptor via the dominant Gs␣/cAMP pathway nor compete for TSH binding (79,80). These "neutral" antibodies were observed to inhibit TSHR cleavage into subunits (33) using the flow cytometric, dual mAb approach (80).…”
Section: Neutral Autoantibodiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, Sande et al reported differences in the kinetics of intracellular cAMP [29] and inositol-1,4,5-triphosphate production [30] when TSHR was stimulated with TSH or TRAb. Although the mechanisms of these effects have not been elucidated, we consider that differences of TSHR reactions such as multimerization [31] or post-translational processing [32] against TSH or TRAb stimulation might participate in those phenomenon. In the future, it is necessary to clarify the detailed mechanisms responsible for such TSHR conformational changes and their relationships with thyrocyte function.…”
Section: Effects Of Monoclonal Tsbab Derived From a Patient With Ime mentioning
confidence: 99%